Case Report: Tricuspid Annuloplasty for Right-Sided Congestive Heart Failure Secondary to Pulmonary Hypertension in a Dog - Mizuno, Takeshi; Sasaki, Kenta; Suzuki, Sayaka; Nagao, Itsuma; Isayama, Noriko (Frontiers in Veterinary Science, 2022)
An 11-year-old, 12.3-kg, female Miniature Dachshund was presented to our institution with ascites of unknown etiology. The dog had been administered moxidectin for 3 years to treat a heartworm infection. Thoracic radiographs showed enlargement of the right heart. Echocardiography revealed right atrial and ventricular dilatation as well as flattening of the interventricular septum. Heartworm was identified in the main pulmonary artery, which was dilated. Tricuspid regurgitation (TR) was observed using color Doppler ultrasonography, and 2.5 L of ascites were removed. The dog was diagnosed with pulmonary hypertension, severe TR, and right-sided congestive heart failure. Except at the initial site, heartworm was not detected using echocardiography, and the antigen test was negative. However, pharmacological treatment did not improve the right-sided congestive heart failure. Instead, De Vega tricuspid annuloplasty (TAP) was performed on the beating heart under cardiopulmonary bypass with the owner's consent. Sutures terminated between the two commissures in the middle of the annulus and were secured using another pledget. Annular reduction was performed by tying down the plication suture while the cylindrical sizer was inserted into the tricuspid valve orifice. The size of the cylindrical sizer was 16 mm, which was set based on the height and width of the septal leaflet. A 6-month follow-up showed a reduction of TR and right-sided volume overload with no evidence of ascites retention/recurrence or any other complication. Our findings indicate that TAP may be a valid treatment option for dogs with right-sided congestive heart failure caused by secondary TR.